Adaptive Fuzzy Sugeno Large of Maxima Optimization for Gas Turbine Biofuel Speed Controllers - Ali M.; Simic M.; Alrahman A.; Nagi F. (Elsevier B.V., 2023)
Biofuels; Combustion; Controllers; Fossil fuel deposits; Fossil fuels; Fuels; Gases; Knowledge based systems; Ship propulsion; Speed; Speed control; Alternative to fossil fuels; Electrical power generation; Fossil fuel resources; Fuzzy controllers; Fuzzy Sugeno Large of Maxima; Gas turbine modeling; Renewable energies; Speed controller; Gas turbines